2014
DOI: 10.1089/mdr.2013.0073
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Molecular Characterization of Fluoroquinolone Resistance inEscherichia coliIsolates from Dairy Cattle with Endometritis in China

Abstract: Fluoroquinolones are frequently used to treat infectious disease that is caused by Escherichia coli in dairy cattle. However, fluoroquinolone resistance occurs and is due either to chromosomal mutations in the bacterial topoisomerase genes and/or to plasmid-mediated resistance genes. The purpose of this study was to determine the prevalence and molecular characteristics of fluoroquinolone resistance determinants in E. coli strains (n=148) isolated from dairy cattle with bovine endometritis in Inner Mongolia (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 41 publications
3
16
2
Order By: Relevance
“…Nowadays, antibiotics have become the first choice of the treatment for liver inflammation. However, many reports have shown that the prevalence of multi-antibiotic Escherichia coli increased markedly in animals (Zhao et al, 2014 ). Therefore, we need to put out new prophylactic and therapeutic approaches to treat liver inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, antibiotics have become the first choice of the treatment for liver inflammation. However, many reports have shown that the prevalence of multi-antibiotic Escherichia coli increased markedly in animals (Zhao et al, 2014 ). Therefore, we need to put out new prophylactic and therapeutic approaches to treat liver inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, methods are needed to eradicate the causative bacteria earlier and control inflammation. Although antibiotics have been effective, increasing drug resistance and concerns about food safety limit their use (Malinowski et al, 2011;Zhao et al, 2014;Mackeen et al, 2015;Ward and Duff, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…One isolates (CM4) with a single mutation in gyrA did not exhibit any mutation in parC . This is because according to the currently accepted alternating-target model, high-level fluoroquinolone resistance in E. coli develops by stepwise acquisition of target mutations, in which DNA gyrase is the primary target and topoisomerase IV is the secondary target for fluoroquinolones in E. coli [ 21 - 23 ]. Most common mutation noticed were at S83⟶L and D87⟶N of gyrA and S80⟶I of ParC in our study ( Table-3 ).…”
Section: Resultsmentioning
confidence: 99%